The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1097/00000478-200012000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Histologic and Immunohistologic Findings and Prognosis of 40 Cases of Gastric Large B-Cell Lymphoma

Abstract: It has been considered that gastric large B cell lymphoma mainly consists of mucosa-associated lymphoid tissue lymphoma (MALToma) with large cell transformation. However, debate continues about the cell lineage. We analyzed 61 operated cases of gastric B cell lymphoma, mainly focusing on 40 cases of diffuse large cell lymphoma (DLCL). Immunohistologically, two cases were classified as CD10-positive follicular lymphoma, 19 cases were low-grade MALToma, 11 CD10-negative DLCL with a component of low-grade MALToma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
24
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 17 publications
5
24
1
4
Order By: Relevance
“…Some studies using immunohistochemical methods have found CD10 expression to be associated with significantly improved OS. 20,23,28,38 Likewise, we found that CD10 expression predicts for better OS. However, given the variability of outcomes in these retrospective studies, it is doubtful that CD10 alone can be used to predict survival in DLBCL.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Some studies using immunohistochemical methods have found CD10 expression to be associated with significantly improved OS. 20,23,28,38 Likewise, we found that CD10 expression predicts for better OS. However, given the variability of outcomes in these retrospective studies, it is doubtful that CD10 alone can be used to predict survival in DLBCL.…”
supporting
confidence: 51%
“…18 Other studies have reported that bcl-6 expression predicts for better OS. 20,24,30 We found that bcl-6 expression by immunohistochemistry predicts for both better OS and EFS. Furthermore, bcl-6, in conjunction with CD10 and MUM1, is a useful marker to identify the GCB phenotype.…”
mentioning
confidence: 71%
“…It is unclear how these studies apply to the assessment of gastric DLBCL, which shows much better prognosis than nodal disease, perhaps because most cases are of early stage (I/II). In gastric DLBCL, only three studies have shown the prognostic value of immunoexpression of CD10 (41,42), BCL6 (7,41), or GCB/non-GCB phenotyping (7) in a relatively small number of cases. In our large study, classification of all cases by GCB/non-GCB subgroup or by expression of CD10, BCL6, or MUM1 did not correlate with OS or EFS.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Many markers have been used to segregate the different groups in regard to their cell of origin and the impact on prognosis and clinical behavior. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] However, it is now accepted that the expression of CD10, Bcl-6 and MUM1 can be used to subclassify diffuse large B-cell lymphoma into germinal center B-cell-like and nongerminal center B-cell-like groups. Thus, it has been shown that the combined expression, or lack thereof, of CD10, Bcl-6 and MUM1 is the best immunohistochemical approach to subclassify diffuse large B-cell lymphoma into two major prognostically different categories using the method of Hans et al 26 Those with CD10 and/or Bcl-6 expression and lack of MUM1 have a germinal center B-cell-like phenotype and better overall survival; the other group, with a CD10-negative/Bcl-6-negative/MUM1-positive immunophenotype, has nongerminal center B-cell-like differentiation and worse overall survival.…”
Section: Discussionmentioning
confidence: 99%